Soybean Reduce Menopause Symptoms In Menopause Women - Yulia Fitri (Science Midwifery, 2022)
the quality of life with the appearance of menopausal symptoms and increases the risk of cardiovascular disease. Giving soy has the potential to reduce various symptoms and complaints of menopause because of its phytoestrogen content. This study aims to determine the effect of soy on menopausal symptoms. . quasi-experimental research design with pre-post control. The sample was selected using a purposive sampling technique with the criteria that they have experienced menopause for 1 year, are sexually active, have normal weight. The instruments used are observation sheets and MRS. Soybean was given for 30 days. Data analysis using T-Test . The results showed a significant difference in somatic and psychological symptoms after intervention (p = 0.00) while urogenital symptoms were not significant (p = 0.054) Giving soy reduces somatic and psychological menopausal women. It is necessary to research the effect of giving soy to menopausal women who are obese because of the different estrogen levels in this group.